TRADISI DOU SANDIK: CERMIN IDENTITAS GUYUB TUTUR BIAK NUMFOR, PAPUA - Hugo Warami (Balai Bahasa Provinsi Papua, 2019)
Dou Sandik tradition of Biak Numfor speech community (GTBN), Papua is the integration of speech language packed with slick as a form of expression of the human soul to God and His work of creation. What is presented through a cycle Dou Sandik tradition of cosmic life and death. Dou sandik tradition ogled as the strengthening of media characters, namely: (1) as a product and practice of GTBN describing his view of self, nature (the world), and God, (2) as a form of interaction with God langue and parole, (3) as pockets of cultural values that precipitate narrative meaning and function of language, and (4) as a medium that can enclose an entity (outward unity) on the expression of life with respect to the portion crophos and religious content. As a reflection of identity, tradition is an attempt Dou Sandik disclosure of ideas, ideas, and the contents of the mind, as well as to reflect the reality of the experience of his successor. This tradition is seen in the structure involving the roles of the process, participants traditions, circumstances, prosesif, stative, active, kala, workshops, and how. Tradition is also used to build and maintain social relationships, to express social roles and communication roles created by Dou Sandik speech itself.